2018
DOI: 10.3846/tede.2018.5487
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Foreign Direct Investment in the Visegrad Group Countries After the Eu Enlargement

Abstract: Considering the role of foreign direct investment (FDI) inflows in the sustainable development of a country, the main aim of this paper is to identify some macroeconomic factors that positively or negatively influence FDI in Visegrad group countries after the European Union (EU) enlargement in 2004. We employed two types of approaches in our analysis: i) time series and ii) panel data approach. According to the generalized ridge regressions estimated in Bayesian framework, the perceived corruption was a factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…: Boghean, State, 2015). Furthermore, Su et. al (2018) have analysed the V4 countries post-EU accession and identified a significant relationship between FDI and high-skilled labour force.…”
Section: Discussionmentioning
confidence: 97%
“…: Boghean, State, 2015). Furthermore, Su et. al (2018) have analysed the V4 countries post-EU accession and identified a significant relationship between FDI and high-skilled labour force.…”
Section: Discussionmentioning
confidence: 97%
“…Cicak & Soric (2015) found that FDI Granger has caused GDP growth in most of the ten European transition countries that were examined. For the period 2005-2016, Su et al (2018) found a significant relationship between FDI, the corruption index and a labour force with advanced education, but only in the long term in the Visegrad group countries (Poland, Hungary, Czech Republic and Slovakia) after the EU enlargement. Stanisic (2008) did not find a positive correlation between FDI and economic growth using a sample of seven countries of Southeast Europe over the period [1997][1998][1999][2000][2001][2002][2003][2004][2005][2006].…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…FDI is also seen as a way to stimulate the economic growth of underdeveloped regions, e.g. : through the creation of new jobs by foreign investors (Petricevic & Teece, 2019;Su et al, 2018;Altomonte & Ottaviano, 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%